Right radicalism: A luxury good for globalization losers in equal societies? - Ulrichsen, David Vestergård; Madsen, Emil Bargmann (Politica, 2018)
Electoral support of radical right parties (RRPs) varies significantly between European countries. In Denmark and the Netherlands, these parties enjoy electoral popularity, while similar support is absent in Portugal and Estonia. We investigate whether economic inequality affects the support of RRPs, and whether the effect is most pronounced among losers of economic globalization. Finally, we test if the association strengthened after the onset of the economic crisis in 2008. Using multilevel cross-sectional data from 16 European countries in 2006 and 2010, we show that economic inequality decreases support for RRPs, especially among losers of globalization. We argue that inequality increases the impact of voters’ economic interests on their party choice and decreases the importance of social cultural issues. Therefore fewer people will vote for RRPs who primarily mobilize voters on social cultural issues.